Moral Consensus, Rights and Efficiency in the Economic Analysis of Law. (28th September 2019) - Chapman, Bruce
Abstract: The primary value that grounds the determination of rights within economic analysis of law is Kaldor–Hicks efficiency. This is a value that, while it claims a Paretian pedigree, can, if pursued systematically and without qualification, lead to an outcome where everyone in some society or some organisation is worse off than they might otherwise have been. Perhaps this should not be a surprise. After all, Amartya Sen showed many years ago that individual rights and the Pareto principle could conflict; this would appear to include Kaldor–Hicks efficient rights. What is more surprising is that to choose welfare over rights as the basis for supporting Kaldor–Hicks efficiency, as the economist is inclined to do, commits the economist to taking the same position on the legal enforcement of positive morality that Patrick Devlin developed more than half a century ago in his debate with HLA Hart.